The crisis of 2008 and the rise of the Slovenian consolidation state - Hočevar, Marko (Teorija in praksa, 2021)
The purpose of the article is to explain the creation of the Slovenian debt state and its transformation into a consolidation state after the crisis of 2008. When the crisis struck Slovenia in 2009, the banking system was near collapse. Through the recapitalisations of the banking system the public debt began to grow. After a couple of years and under the structural pressures of rating agencies and pressures from the EU, the Slovenian state had to adopt austerity measures to consolidate its public finances, while limiting the scope of democracy. The main finding of the article is that the crisis of 2008 fundamentally changed the Slovenian state
Keywords: capitalist state; consolidation; debt; democracy; demokracije; državni dolg; javne finance; kapitalistična država; konsolidirajoča se država; zadolženost